VIBRATIONS OF ABRIKOSOV VORTICES IN SUPERCONDUCTORS - Taylanov, Nizom; Toshpulatova, Dildora; O’rozov , Abdixoliq; Narimanov, Bahodir (Физико-технологического образование, 2021)
In this work, the phenomenon of oscillation of the vortex matter as a result of thermomagnetic instability in a superconductor is theoretically investigated. The spatial and temporal distributions of small thermal and electromagnetic perturbations in a plane semi-infinite superconducting sample are studied. Based on the system of equations for temperature, magnetic induction, and vortex motion, a dispersion relation was obtained that determines the growth (or decay) increment of small perturbations. It was shown that, under certain conditions, depending on the values of the parameters of the system, jumps - oscillations of the magnetic flux is observed.